Développer un territoire périurbain à faible potentiel par la reconversion de gravières ? - Dominique Charrier; Jean Jourdan (Territoire en Mouvement)
As part of the conversion of industrial quarries in a village of 550 inhabitants in the department of the Oise, the Lafarge-Granulats company and local authorities examined the possibilities of developing and operating a “Sport-Nature” recreation centre. Based on a logic of innovation, this project is part of a development plan based on local tourism and activities in peri-urban areas. As such, it exposes the conditions that “low potential” areas and/or those with significant constraints (rural areas, developing countries, urban areas in difficulty, areas exposed to natural risks, etc.) need to meet in order to develop innovative projects. The contribution, based on a two-year study (2010, 2011), analyses the involvement of players in an original public/private partnership configuration because of the industrial company’s obligation to redevelop the area used. It highlights the complexity of the levels concerned and identifies the conditions required to synergise different interests that have to converge. It shows that in this peri-urban context, while this project seemed to be the only means for developing the area, it also met with resistance because of the tourism aspect created by the blend of “Sport and Nature”. The contribution underscores the importance of “local sport dynamics” that combine the specifics of sporting and artistic physical activities with local contexts, to combinations of public, private and association players (from different sectors) and political will applied to the regions. It confirms that the economic and political stakes at the micro-territorial level are just as complex and intertwined as those identified on larger territorial scales.